A Blockchain-enabled System to enhance Food Traceability in Local Food Supply Chains (FSCs) suitable for Small Co-operatives in South Africa - Kanjere, Julian (School of Economics, 2021)
Food is vital to human life. Therefore, ensuring its safety as it moves from producer to consumer in food supply chains (FSCs) is essential. This can be achieved through the use of food traceability technology which enables track and trace of produce within a FSC. Recently, blockchain technology (BCT) has shown great potential to enhance traceability in FSCs, owing to its ability to securely store data in a decentralised and tamper-evident manner. However, it appears that research on blockchain-enabled food traceability exists primarily within the context of large FSCs, whilst scarce for local FSCs in which traceability is often an inefficient and manual process. Given this background, this exploratory research is carried out, to investigate whether a blockchain-enabled system can be used to improve traceability in local FSCs. To do this, we (i) collaborate with Oranjezicht City Farm Market (OZCFM) - a farmers market in Cape Town, the smallholder farmers that supply OZCFM with fresh local produce and the OZCFM patrons that purchase the produce; (ii) map out the local FSC by conducting observations and running surveys with the aforementioned actors; (iii) design, develop and pilot FoodPrint - a web based and blockchain-enabled food traceability application. During the pilot within the OZCFM-related local FSC, FoodPrint is used to capture data on the harvest, transportation and storage of produce; and reveal produce provenance at destination by scanning of supplier-produce specific quick response (QR) codes. We find that FoodPrint provides tamper-evident traceability and authentic transparency of produce related data to the local FSC actors. Further, we note that scanning a FoodPrint QR code for produce provenance does not enhance the consumers trust of the local FSC, as it pre-exists. This implies that local FSCs with existing and functional trust mechanisms do not benefit from trust-enhancing mechanisms such as blockchain-enabled traceability. Future work may consider data privacy in FSCs and automating FSC data entry to reduce the risk of fraud.